Seed arrival in tropical forest tree fall gaps. Issue 7 (1st July 2013) - Puerta-Piñero, Carolina; Muller-Landau, Helene C.; Calderón, Osvaldo; Wright, S. Joseph
Abstract : Tree deaths open gaps in closed‐canopy forests, which allow light to reach the forest floor and promote seed germination and seedling establishment. Gap dependence of regeneration is an important axis of life history variation among forest plant species, and many studies have evaluated how plant species differ in seedling and sapling performance in gaps. However, relatively little is known about how seed arrival in gaps compares with seed arrival in the understory, even though seed dispersal by wind and animals is expected to be altered in gaps. We documented seed arrival for the first seven years after gap formation in the moist tropical forests of Barro Colorado Island (BCI), Panama, and evaluated how the amount and functional composition of arriving seeds compared with understory sites. On average, in the first three years after gap formation, 72% fewer seeds arrived in gaps than in the understory (207 vs. 740 seeds·m −2 ·yr −1 ). The reduction in number of arriving seeds fell disproportionately on animal‐dispersed species, which suffered an 86% reduction in total seed number, while wind‐dispersed species experienced only a 47% reduction, and explosively dispersed species showed increased seed numbers arriving. The increase in explosively dispersed seeds consisted entirely of the seeds of several shrub species, a result consistent with greater in situ seed production by explosively dispersed shrubs that survived gap formation or recruited immediately thereafter. Lianas did relatively better in seed arrival into gaps than did trees, suffering less of a reduction in seed arrival compared with understory sites. This result could in large part be explained by the greater predominance of wind dispersal among lianas: there were no significant differences between lianas and trees when controlling for dispersal syndromes. Our results show that seed arrival in gaps is very different from seed arrival in the understory in both total seeds arriving and functional composition. Differential seed arrival in gaps will help to maintain wind‐dispersed, explosively dispersed, and possibly other understory species in the community of plants that regenerate in gaps.